(untitled) (KULT_online, 2021)
Daniela Lai’s book Socioeconomic Justice makes a compelling case for the expansion of Transitional Justice mechanisms to include justice claims made within the community in post-war contexts, where jobs and livelihoods are rarely seen as a priority. This book guides us through a maze of international intervention, war-time socioeconomic violence and its lingering effects in peacetime, along with justice claims after the 2014 protests, by studying political economy of war and peace on one side and redefining transitional justice mechanisms on the other.